FEATURES OF THE RS1799983 POLYMORPHISM OF THE ENOS GENE IN WOMEN WITH GLANDULAR ENDOMETRIAL HYPERPLASIA - Abdulatipova, F.A.; Kurbanov , B.B.; Kurbanov , D.D. (JOURNAL OF EDUCATION AND SCIENTIFIC MEDICINE, 2025)
The purpose of the study: was to study the Glu298Asp (rs1799983) polymorphism in the eNOS gene in women with glandular endometrial hyperplasia. Materials and methods: we conducted a study in 88 women with endometrial hyperplasia, which were divided into 2 groups: Group 1 (main) 49 women without atypia, Group 2 - 39 women with atypia. The control group consisted of 50 healthy women. The age of the examined women ranged from 21 to 47 years. Results: In the main group, the Glu allele of the rs1799983 polymorphism of the eNOS gene was represented in 78.41%, while the Asp allele was 21.59%. In the control group, the frequencies of the Glu and Asp alleles were 82.78% and 17.22%. In the main group, the Glu/Glu, Glu/Asp and Asp/Asp genotypes were detected in 63.64%, 29.55% and 6.82% of cases, respectively. Conclusions: The contribution of the RS1799983 polymorphism of the eNOS gene in women with glandular hyperplasia of the endometrium has been proven.